Collaboration Between UKS And Puskesmas Services In Early Childhood Growth And Development Supervision At Ba ‘Aisyiyah 3 Merden - Ami Wahyuni, Isti; Sunarko, Asep; Farida, Nur (AJIRSS: Asian Journal of Innovative Research in Social Science, 2024)
Community service activities aim to provide assistance in optimizing the School Health Efforts (UKS) to create healthy students. Schools can realize this by activating the school health business program which aims to improve optimal health so that it can maximize the potential and achievements of children in learning. The purpose of this community service is assistance to optimize UKS. The method of implementing community service activities in facilitating the optimization of UKS is through observing conditions and inventorying the needs for space and facilities for UKS and identifying the implementation of the UKS Trias. The instrument for measuring results uses a questionnaire. The results of the activity showed that the existing UKS room was not permanent and was still one with the school principal's room. The medical equipment at the UKS only consists of simple beds and first aid kits. The implementation of the UKS Triassic found that the implementation of health education and counseling in schools was included in the poor category; the implementation of health services is included in the less category; and the implementation of a healthy school environment is included in the less category so the solutions provided are assistance in procuring UKS space and equipment and socialization of the UKS Triassic. UKS activities are important for school health efforts, so monitoring and evaluation need to be carried out on an ongoing basis.